REPRESENTASI SENSUALITAS DALAM IKLAN OBAT KUAT DI LOKAPASAR INDONESIA - Mad Yahya; Tsalits Syafa’atun Nashiroh; Sulistyowati (Universitas Warmadewa, 2026)
This article examines advertisements for male enhancement drugs on online marketplaces that tend to display aspects of male and female sensuality. The signs of sensuality in the advertisements are analyzed using Roland Barthes’ semiotic approach. This study employs a qualitative methodological approach. The data sources consist of advertisements for male enhancement drugs found on various popular online marketplaces in Indonesia. The research data comprise 40 advertising posters collected through literature review, documentation techniques, and screenshot capture. After the data were collected, categorization, data reduction, and analysis were conducted based on Roland Barthes’ semiotic theoretical framework. The results show that advertisements for male enhancement drugs in online marketplaces tend to exploit the sensuality of both men and women, which is manifested through visual components and advertising text. At the level of denotation, advertisements are generally realized through visual elements such as images of women and/or men, product images, logos, colors, and illustrations, while the textual components include linguistic units in the form of words, phrases, and sentences. At the level of connotation, male enhancement advertisements construct meanings related to sensuality, such as female seduction, assumptions of sexuality associated with white-skinned individuals, husband–wife romantic relationships, and male virility. These aspects of sensuality are reinforced through the use of hyperbolic language in the advertisements. Meanwhile, the myths embedded in male enhancement advertisements tend to associate male sexual satisfaction with certain socio-cultural assumptions, including female sexual satisfaction, family harmony, masculinity, and male superiority. The myths also represent male virility as being measured by the ability to dominate women.